“QUORUM SENSING” AND VIRULENCE IN Pseudomonas aeruginosa (Review) - N Arráiz (Kasmera, 2001)
In recent years, interest in the study of communication has grown intercellular bacterial and regulatory mechanisms of the expression of certain genes in response to high cell densities. The "social" behavior of bacteria is emerging as a model regulatory integral that trains these organizations to face various environmental stress conditions, which becomes very important in the case Particular of pathogenic bacteria growing in host tissues.